The Gattis celebrate their 40th wedding anniversary (Raton Range Raton, New Mexico, 1982)
Newspaper Article on the 40th Anniversary of Larry and Ann Gatti.
Master list item #: 90
File location is in the Raton File Cabinet
Keywords: Gatti, Larry; Gatti, Ann; Gatti, Stan; Schulte, Irma; Rea, Domenic; Carson, Sharon Ruth; Gatti, Cheryl Gay; Gatti, Michael John; Gatti, Allen Larry; Gatti, Stanlee Re; Beck, Laresa Ann; Beck Ginger Marie; Carson, Tom; Carson, Matthew Thomas; Carson, Christopher Ryan; Simovich, John; Simovich, (Mrs.); Raicevich, Edgar; Raicevich, (Mrs.); Kelly, U.B.; Incetti, Joe; Incetti, Mary Jane; Tomsick, John; Shelter, U'Berta; Olguin, Dolores; Arcangeli, Everni; Dabovich, Danny; Milavec, Mary; Pompeo, Asunta; Owensby, Fred; Owensby, (Mrs.); Patterson, Lena; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Ft. Collins, Colorado; Loveland, Colorado; Albuquerque, New Mexico; Boulder, Colorado; San Francisco, California; Eagle Nest, New Mexico; Meeker, Colorado; Maxwell, New Mexico; Folsom, New Mexico; Nampa, Idaho